2023
DOI: 10.1039/d3tc00401e
|View full text |Cite
|
Sign up to set email alerts
|

Broadband yellow and white emission from large octahedral tilting in (110)-oriented layered perovskites: imidazolium-methylhydrazinium lead halides

Abstract: Hybrid organic-inorganic perovskites (HOIPs) are presently on the cutting edge of contemporary materials chemistry providing excellent and tuneable optoelectronic properties. Here we report the synthesis, crystal structures, linear optical as...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
36
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 14 publications
(40 citation statements)
references
References 79 publications
4
36
0
Order By: Relevance
“…, 0.27 and 0.33 eV, was obtained for IMMHyPbBr 4 and IMMHyPbCl 4 compounds, in which the relaxation was assigned to movements of the MHy + cation. 46 We suppose, therefore, that the relaxation process seen in the MA 1− x MHy x PbI 3 samples has a different origin than that reported for pure MAPbI 3 , i.e. , it may be related to MHy + movements.…”
Section: Resultsmentioning
confidence: 78%
“…, 0.27 and 0.33 eV, was obtained for IMMHyPbBr 4 and IMMHyPbCl 4 compounds, in which the relaxation was assigned to movements of the MHy + cation. 46 We suppose, therefore, that the relaxation process seen in the MA 1− x MHy x PbI 3 samples has a different origin than that reported for pure MAPbI 3 , i.e. , it may be related to MHy + movements.…”
Section: Resultsmentioning
confidence: 78%
“…It was previously reported that the 1D and 2D hybrid perovskites with corrugated inorganic sublattices exhibit efficient broadband light emissions. 71–73 The broadband light emissions mainly arise from distorted excited states and self-trapped excitons originating from strong electron–phonon coupling with the emission linewidth related to the distortion level of the [PbX 6 ] octahedron. 74–77…”
Section: Resultsmentioning
confidence: 99%
“…They also show that MHy + cations have unusual ability to form lead halides of vast structural diversity and properties, i.e. , 3D (MhyPbX 3 , X = Cl, Br) 6–8 and quasi-2D RP (BA 2 MHy 2 Pb 3 Br 10 , BA + = butylammonium) 58 with MHy + serving as a ‘perovskitizer’ cation, 2D of formula MHy 2 PbX 4 (X = Cl, Br, I) 16,46,47 and the 2D ACI phase (IMMHyPbX 4 , X = Cl, Br, IM = imidazolium) 22 with MHy + as a ‘spacer’ cation and 1D (MHyPbI 3 ) 45 and 0D (this work), in which MHy + cations separate inorganic chains or PbX 6 4− octahedra.…”
Section: Discussionmentioning
confidence: 99%
“…12 This approach is also an efficient way for tuning photoluminescence (PL) colour as well as inducing polar (ferro- or antiferroelectric) order and second-order NLO properties. 15,18,19,21,22 Although numerous examples of layered lead halide perovskites comprising two cations have been reported, we are not aware of any mixed-cation analogues in the family of 1D and 0D lead halides.…”
Section: Introductionmentioning
confidence: 99%